Identifikasi Potensi Bahaya dan Risiko Keselamatan dan Kesehatan Kerja pada Pabrik Tahu House Of Tofu - Yofira Sintya Dewi; Agung Ikhssani (Puslitbang Sinergis Asa Professional, 2021)
Occupational Health and Safety (K3) is generally defined as the science of anticipating, recognizing, evaluating and controlling hazards arising in or from the workplace that may interfere with the health and well-being of workers, taking into account the possible impact on the environment and the surrounding community. The scope is quite broad, covering a large number of disciplines and many hazards in the workplace and the environment.The International Labor Organization (ILO) released data in 2020 that globally, more than 2.78 million people die from workplace-related accidents or diseases, which means one death every fifteen seconds Measures and strategies designed to prevent, control, reducing or eliminating occupational hazards and risks have been developed and implemented over the years to keep pace with technological and economic changes. Work and industrial accidents are all caused by preventable factors that can be eliminated by applying known and available measures and methods. This is indicated by the continued decline in accident rates in industrialized countries. Therefore, the implementation of prevention strategies offers significant human and economic benefits. However, occupational accidents and diseases are still too frequent and their cost in terms of human suffering and economic burden continues to be significant. This study discusses the level of occupational accidents and occupational diseases obtained by conducting a walk-through survey at the tofu factory